MANAJEMEN KONFLIK DALAM MENGATASI PROBLEMATIKA GURU DI LEMBAGA PENDIDIKAN - Tio Ari Laksono; Imania Fatwa Izzulka (Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract: Conflict Management In Overcoming Teacher Problems In Educational Institutions This paper aims to explain the problems of teachers and problem solving of any problems related to problems in the world of education, both related to technical matters, concepts, or planning. The methodology in this paper is using library research, while data collection is done by reviewing and exploring several books, journals, articles, and other sources of data and information deemed relevant to the study. The findings in this study are the occurrence of various problems faced by teachers. In general, the problems experienced by teachers can be divided into 2 major groups, namely internal problems (problems originating from the teacher concerned), and external problems (problems originating from outside the teacher). The solutions can be detailed as follows: 1) Increasing teacher professionalism; 2) Increasing teaching eligibility and teacher welfare and; 3) Provision of living allowances.